2011
DOI: 10.1039/c0jm02461a
|View full text |Cite
|
Sign up to set email alerts
|

High concentration few-layer graphene sheets obtained by liquid phase exfoliation of graphite in ionic liquid

Abstract: In the present work, the use of a commercial ionic liquid as a convenient solvent medium for graphite exfoliation in mild and easy conditions without any chemical modification is presented. To confirm the presence of few layer graphene, its dispersion, which exhibits Tyndall effect, was characterized by Raman and UV spectroscopies, and atomic force and field emission electron microscopies. It is noteworthy that, by gravimetric analysis, a graphene concentration as high as 5.33 mg ml À1 was determined, which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
235
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(247 citation statements)
references
References 38 publications
4
235
0
2
Order By: Relevance
“…[36][37][38][39][40][41][42][43][44][45][46][47] This work has contributed greatly to our understanding of the dispersion process, our practical approach to dispersion and the number of solvents available to graphene researchers.…”
mentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46][47] This work has contributed greatly to our understanding of the dispersion process, our practical approach to dispersion and the number of solvents available to graphene researchers.…”
mentioning
confidence: 99%
“…It also offers graphene yields as high as 5.33 mg/mL. Because of the use of an ionic liquid (1-hexyl-3-methyl-imidazolium hexafluorophosphate or HMIH), this process is stable and green [51]. Sodium dodecylbenzene sulfonate (SDBS) also tends to stabilize graphene layers and keeps them from aggregation [53].…”
Section: Sonicationmentioning
confidence: 99%
“…), where graphene can be separated from graphite with the help of centrifugation [49]. NMP or other ionic liquid can be used in such process [50,51]. A singlecycle yield of up to 5 % is obtainable from this process and about 70 % of the graphene obtained by this process is 1 nm thick having electrical conductivity of up to 5000 S·m −1 [52].…”
Section: Sonicationmentioning
confidence: 99%
“…Zheng et al has reported solvothermal route to prepare graphene by direct exfoliation using oleylamine as a solvent as well as stabilizing agent [16]. Nuvoli et al has used a commercial ionic liquid 1-hexyl-3-methylimidazolium hexafluorophosphate (HMIH), as a convenient solvent medium for graphite exfoliation in mild and easy conditions without any chemical modification [17]. This method resulted in few layer graphene with a concentration as high as 5.33 mg/ml, which is the highest value reported so far in any solvent.…”
Section: Introductionmentioning
confidence: 99%